Application of Communication in The Metatah Traditional Ceremony in Bali - Nofrianti, Mami; Alisa, Della Nindia (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
Traditional ceremonies in Bali are an important part of the culture and identity of its people. Communication in this traditional ceremony involves various elements such as symbols, movements, music, and ritual language rich in meaning. This research explores the dynamics of communication in Balinese traditional ceremonies, focusing on the role of symbols and rituals in transmitting values, norms, and cultural identity to future generations. This research uses a literature study method with a qualitative approach to explore communication in Balinese traditional ceremonies. Through the analysis of various literature sources, including books, articles, and related publications, this research gains deep insights into the role of communication in the context of Balinese culture. By integrating communication theory, cultural anthropology, and traditional ceremony studies, this research aims to depict the complexity of ritual and symbolic communication in Balinese traditional ceremonies and its impact on the sustainability of local culture. The ultimate goal is to provide a more comprehensive understanding of how communication plays a key role in preserving and strengthening cultural heritage.